MENGOPTIMALISASIKAN PELAYANAN PEMBUATAN AKTE KELAHIRAN - Hayat Hayat; Laily Hidayah (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2017)
The purpose of this study is to optimize the public service in the birth certificate. To optimize the service birth certificates, needed komprehenship concept in its implementation so that the implications are positive. Policy leaders have a major impact on the change for the better in order to maximize and optimize the performance of public services in the manufacture of a birth certificate. Public services are optimal, of course, have an indication of quality service and excellence. Achievement of good governance can not be separated from the strategic role of qualified personnel, professional and accountable in the performance of public services. Apparatus public services become a central point in optimizing the performance of public services. This research method survey conducted by the research object, and then conducted detailed interviews to service providers and service users. In addition, the data also prepared documentation as supporting data. Furthermore, analyzing the birth certificate of service based on the survey results, informations the interviewee as well as support for document data that has been sorted and selected to complement the accuracy of research data. The results showed that birth certificates services performed in the Department of Population and Civil Registration District has been done on an ongoing basis.